Idosos vivendo com HIV/AIDS: vulnerabilidade e redes sociais em Belo Horizonte (MG), 2013 - Marília Borborema Rodrigues Cerqueira (2014)
The objective of this thesis is to identify the factors associated with the vulnerability of the elderly aged 60 years or more to HIV/AIDS, based on in-depth interviews aiming to: i) understand the dynamics of epidemic HIV/AIDS among the aged in Belo Horizonte, addressing aspects related to the epidemiologic and individual context; ii) verify the perceptions and behaviors of elderly related to HIV/aids; iii) record and analyze information about the social network in which they are inserted. The research question was which factors are associated with the vulnerability of the elderly to HIV/AIDS, considering the demographic dynamics and the aging population? In line with the conceptual framework adopted in this thesis, vulnerability-generating intersubjective contexts were addressed. The study universe were the elderly living with the virus, treated at Hospital Eduardo de Menezes da Fundação Hospitalar do Estado de Minas Gerais. Interviews with 20 older adults (12 women and 8 men), who signed a consent form and were considered mentally fit were performed. The methodology also included previous analysis of data collected from DATASUS and from medical records of the aged with HIV/AIDS treated at the same hospital. The aged interviewed showed low level of education, low income, are or were in marital union, and have perceptions and behaviors grounded in structural gender relations with asymmetry of power, therefore, showing low responsiveness to vulnerability. Most aged interviewed are sexually active, but few of them declared to protect themselves by using condoms. Adherence to antiretroviral therapy has close relation with the way of contracting the virus: aged women who were betrayed have a poor adherence to the HAART and are angry and depressed. Social networks become support networks, which go beyond the household, revealing reciprocal exchanges between the aged and family. Some aged living with HIV/AIDS play an important role in the social network, as counselors, for example. Regarding the programmatic level, many aged highlighted that they have never seen a program focused on their generation, and the lack of information reaches all levels of vulnerability. The picture revealed by this thesis is worrying because, despite the fact that demographic dynamics and the aging population have already been incorporated into discussions, elderly have been considered as asexual beings. It is expected, in this sense that, this thesis can help to demystify the sexual invisibility of the aged, ensuring them a healthy and continuous sexual life, what is rightfully theirs.